(untitled) (Bangladesh Journal of Microbiology, 2021)
Sonneratia apetala (S. apetala) (Lythraceae) has been investigated for the isolation and characterization of antimicrobial compounds and evaluation of their biological activities. The chloroform extract of the stem bark and different partitionate of the chloroform extracts i.e. Petroleum ether soluble fraction (PESF), Ethyl acetate soluble fraction(EASF), Methanol soluble fraction(MSF) and aqueous soluble fractions (ASF) were subjected to different chromatographic techniques to isolate secondary metabolites. Successive chromatographic separation and purification yielded a total of two compounds identified and characterized as Taraxerone(1) and 5,8-dihydroxy- 6-methoxy-4,9-dioxo-1,3,4,9-tetrahydronaphthol[2,3-c]furan-1-yl acetate (2) by extensive proton NMR spectrum (1H-NMRspectrum) analysis. The different partitionate like PESF, EASF, MESF and ASF were subjected to screen their antimicrobial properties against some selected Gram positive and Gram negative bacteria and fungi, brine shrimp lethality and antioxidant activities. The maximum zone of inhibition of chloroform extract was found against Pseudomonas sp. (16mm). All fractions showed more activity against Gram negative bacteria then Gram positive bacteria. In the brine shrimp lethality bioassay, among all extracts, the petroleum ether and ethyl acetate soluble fraction showed significant lethality having the LC50 value of 7.72 μg/ml. The antioxidant activity was evaluated in terms of determination of free radical scavenging activity (DPPH assay). Among all the extracts of S. apetala the highest free radical scavenging activity showed by (Methanol soluble fraction) MESF with IC50 value 18.0 μg/ml. Bangladesh J Microbiol, Volume 38, Number 1, June 2021, pp 1-5